2011
DOI: 10.1172/jci43114
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 loss of heterozygosity causes vascular tumors and lethal hemorrhage in mice

Abstract: The role of the Notch signaling pathway in tumor development is complex, with Notch1 functioning either as an oncogene or as a tumor suppressor in a context-dependent manner. To further define the role of Notch1 in tumor development, we systematically surveyed for tumor suppressor activity of Notch1 in vivo. We combined the previously described Notch1 intramembrane proteolysis-Cre (Nip1::Cre) allele with a floxed Notch1 allele to create a mouse model for sporadic, low-frequency loss of Notch1 heterozygosity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 46 publications
2
111
0
Order By: Relevance
“…24 Especially in endothelial cells the Notch pathway has been associated with tumor suppressor functions. [13][14][15] Chronic Dll4 blockade as well as loss of Notch1 heterozygosity induce vascular tumor formation. 14,15 In line with these findings, we have recently reported that Notch1 acts as a tumor suppressor gene in LSECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Especially in endothelial cells the Notch pathway has been associated with tumor suppressor functions. [13][14][15] Chronic Dll4 blockade as well as loss of Notch1 heterozygosity induce vascular tumor formation. 14,15 In line with these findings, we have recently reported that Notch1 acts as a tumor suppressor gene in LSECs.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Chronic Dll4 blockade as well as loss of Notch1 heterozygosity induce vascular tumor formation. 14,15 In line with these findings, we have recently reported that Notch1 acts as a tumor suppressor gene in LSECs. 13 In our Notch1 KO mouse model, AS development occurs spontaneously over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA abnormalities in the Notch signalling pathway have been identified in a small series of angiosarcoma patients [151]. Interestingly, pan inhibition of Notch signalling resulted in liver sinusoidal endothelial cell proliferation, intussusceptive angiogenesis, and the formation of hepatic vascular abnormalities, including angiosarcomas, in vivo [152,153].…”
Section: Angiogenesismentioning
confidence: 99%
“…Studies have shown inhibition of Notch1 in mouse models leads to the formation of vascular tumours, including hepatic angiosarcomas [152,153], and the importance of Notch in branching morphogenesis and in regulating endothelial cell expression of receptors such as VEGFR2 and NRP1 [30], identifies an area worth further study. The be assessed in cell viability and cell differentiation assays.…”
Section: Future Workmentioning
confidence: 99%